Sarcopenia screening strategies in older people: a cost effectiveness analysis in Iran - Ali Darvishi; Mohsen Rezaei Hemami; Gita Shafiee; Rajabali Daroudi; Mahsa Mohseni; Farkhondeh Hosseini Shekarabi; Ramin Heshmat (BMC, 2021)
Abstract Background and objectives Sarcopenia is an important age-related disease which can lead to an increased risk of mortality, falls, fractures, and poor quality of life. So, timely detection can be effective in reducing the burden of disease. The aim of this study was to identify the most cost-effective strategy for sarcopenia screening in Iran. Materials and methods We constructed a Markov transition model over a life-time horizon based on natural history. Compared strategies included Sarcopenia scoring assessment models (SarSA-Mod), European working group on sarcopenia in older people (EWGSOP), Mini sarcopenia risk assessment (MSRA) and SARC-F. Parameters values were extracted from primary data and the literature, and the costs and Quality-adjusted life years (QALYs) were calculated for each strategy. Sensitivity analysis of uncertain parameters was also performed to determine the robustness of the model. Analysis was performed using 2020 version of TreeAge Pro software. Results All four screening strategies increased life time QALYs. After removing dominated strategy, the incremental cost per QALY gained for sarcopenia screening varied from $1875.67 for EWGSOP to $1898.33 for MSRA. Our base-case analysis showed that the most cost-effective strategy was EWGSOP and 2nd best was SarSA-Mod with $43,414.3 and $42,663.3 net monetary benefits given one GDP per capita ($5520.311) as willingness to pay, respectively. Sensitivity analysis of model parameters also showed robustness of results. Conclusions The results of the study, as the first economic evaluation of sarcopenia screening, showed that the EWGSOP strategy is more cost-effective than other strategies.